2009
DOI: 10.1055/s-0039-1697448
|View full text |Cite
|
Sign up to set email alerts
|

Caries is Associated with Asthma and Epilepsy

Abstract: ObjectivesThere is evidence of association between systemic diseases and oral conditions, although it is not clear if these are direct or mediated by underlying factors such as health behaviors. The aim of this work was to evaluate whether self-reported systemic diseases were associated with caries experience.MethodsMedical history data and caries experience (DMFT and DMFS; Decayed, Missing due to caries, Filled Teeth/Surface) were obtained from the University of Pittsburgh School of Dental Medicine Dental Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 26 publications
5
24
0
1
Order By: Relevance
“…Meta-analysis suggests that being affected by asthma doubles the risk of caries in both primary and permanent dentition (Alavaikko et al, 2011). Our data confirms the results of the meta-analysis by Alavaikko et al (2011) that suggested an association between higher caries experience and asthma in adults (Anjomshoaa et al, 2009). Individuals with asthma appear to accumulate higher amounts of dental biofilm, as well as higher salivary levels of mutans streptococci (Botelho et al, 2011).…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…Meta-analysis suggests that being affected by asthma doubles the risk of caries in both primary and permanent dentition (Alavaikko et al, 2011). Our data confirms the results of the meta-analysis by Alavaikko et al (2011) that suggested an association between higher caries experience and asthma in adults (Anjomshoaa et al, 2009). Individuals with asthma appear to accumulate higher amounts of dental biofilm, as well as higher salivary levels of mutans streptococci (Botelho et al, 2011).…”
Section: Introductionsupporting
confidence: 92%
“…We have been investigating the possible contribution of genetic variation of enamel formation genes in caries (Deeley et al, 2008; Patir et al, 2008; Shimizu et al, 2012), a disease that leads to demineralization of the enamel. Our data also suggest that asthmatic individuals have more severe caries experience (Anjonshoaa et al, 2009), although recent evaluations of asthmatic children show that recently implemented asthma management and educational programs are reducing caries experience in these children (Lindemeyer et al, 2012). Children with asthma more often have enamel hypoplasia and these clinical defects are consequence of either primary ameloblast defects or defective interactions between odontoblasts and ameloblasts (Musale et al, 2010).…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Both studies suggested the existence of an association between higher caries experience and asthma in adults [8, 9]. …”
Section: Discussionmentioning
confidence: 99%
“…[5360] Promotion of oral health has, therefore, been suggested as a way to promote systemic health, since there is a possible role of oral infections as a risk factor for systemic disease. [61] It is imperative for medical and dental practitioners to take note of these recent findings. The best time to pass this knowledge across in our view is during the training of these professionals.…”
Section: Chronic Periodontitismentioning
confidence: 99%